Egyptian men working abroad: Labor supply responses by the women left behind - Christine Binzel; Ragui Assaad (Institute for the Study of Labor (IZA), 2011)
Female labor force participation has remained low in Egypt. This paper examines whether male international migration provides a leeway for women to enter the labor market and/or to increase their labor supply. In line with previous studies, we find a decrease in wage work in both rural and urban areas. However, women living in rural areas and affected by migration are much more likely to be employed in non-wage activities (i.e. unpaid family work) and subsistence work compared to women in non-migrant households. Furthermore, we find evidence that this labor supply response is driven by the household's need to replace the migrant's labor rather than by a loosening of a financing constraint on family enterprises made possible by the flow of remittances.
urn:nbn:de:101:1-201104134113
Keywords: O15; J22; F22; R23; 330; migration; remittances; labor supply; gender; Weibliche Arbeitskräfte; Arbeitsangebot; Männliche Arbeitskräfte; Internationale Arbeitsmobilität; Rücküberweisung (Migranten); Ägypten